Improving Students’ Speaking Ability on Expressing Plan through Problem Based Learning (PBL) Method - Bahrudin, Dinar Vincy Yunitaka (OKARA: Jurnal Bahasa dan Sastra, 2018)
Tenth-grade students at SMAN 4 Pamekasan faced some problems in speaking. They are difficult to express their ideas in oral form and unconfident when they speak English. It happens because of limitation on vocabulary, and they may never practice speaking. Problem Based Learning (PBL) is a good method to teach Speaking. This research is a Classroom Action Research (CAR). The subject is the 37 students of Tenth-grade students at SMAN 4 Pamekasan. There are two cycles, one meeting in each cycle. The research procedures consist of planning, acting, observing, and reflecting. Field note, observation, documentation, and test were used to collect the data. The result revealed mean scores of preliminary study were 54.46 and the percentage score was 24.32%. The mean score of the test of cycle 1 was 67.84 and the percentage score was 48.64%. The mean score of class in speaking test gained until 80.27 and the percentage score was 86.48%. The improvement of the percentage score students who got equal or greater than KKM from cycle I to cycle II was 37.84%. It concludes that Problem Based Learning Method can improve students’ speaking ability on Expressing Plan of the Tenth Grade at SMAN 4 Pamekasan.